USING BLOG TO ENHANCE ENGLISH WRITING SKILL AMONG HIGH SCHOOL STUDENTS IN THAILAND - Kohsamut, Tinnadit; Sucaromana, Usaporn (PEOPLE: International Journal of Social Sciences, 2017)
This research aimed to examine the effectiveness of using blog with high school students, and investigated students’ perception when they learn writing through the blog.The participants for this study were 50 secondary school students selected by using purposive sampling method. Both quantitative and qualitative data collection and analyses were applied. The quantitative data were collected from the score of pre-test and posttest. The qualitative data were derived from the content analysis of group interviews. The result revealed that students significantly performed better scores on English writing ability test after being taught through the blog. In addition, students showed positive views because using blog was very interesting and it provided more cooperation between teacher and students.